Croatian language resources for NooJ - Kocijan, Kristina (Array, 2010)
This paper presents the Croatian module for NooJ. The module includes Croatian author Vjenceslav Novak and his novel 'Posljednji Stipančići' as a corpus with fully covered dictionary (i.e. zero unknowns). Examples of morphological and syntactic grammars are included together with few examples of dictionary entries and their inflectional and derivational paradigms